2022
DOI: 10.1038/s41598-022-04827-6
|View full text |Cite
|
Sign up to set email alerts
|

Ionic mitigation of CD4+ T cell metabolic fitness, Th1 central nervous system autoimmunity and Th2 asthmatic airway inflammation by therapeutic zinc

Abstract: T helper (Th) cells provide immunity to pathogens but also contribute to detrimental immune responses during allergy and autoimmunity. Th2 cells mediate asthmatic airway inflammation and Th1 cells are involved in the pathogenesis of multiple sclerosis. T cell activation involves complex transcriptional networks and metabolic reprogramming, which enable proliferation and differentiation into Th1 and Th2 cells. The essential trace element zinc has reported immunomodulatory capacity and high zinc concentrations i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…The lung is the gateway for gas exchange between the body and outside world. Following exposure to harmful substances (cadmium, cigarette smoke), zinc levels in the lungs are increased to protect the lung tissue by affecting the functions of certain cells (macrophages, T lymphocytes and neutrophils) [ 38 40 ]. ZIP8 is a zinc transporter that is highly expressed in alveolar epithelial cells and is the main entry point for Cd, a toxic heavy metal and carcinogen that exists in large quantities in cigarette smoke [ 41 ].…”
Section: Protective and Prevention Effect Of Zinc Homeostasis On Lung...mentioning
confidence: 99%
See 3 more Smart Citations
“…The lung is the gateway for gas exchange between the body and outside world. Following exposure to harmful substances (cadmium, cigarette smoke), zinc levels in the lungs are increased to protect the lung tissue by affecting the functions of certain cells (macrophages, T lymphocytes and neutrophils) [ 38 40 ]. ZIP8 is a zinc transporter that is highly expressed in alveolar epithelial cells and is the main entry point for Cd, a toxic heavy metal and carcinogen that exists in large quantities in cigarette smoke [ 41 ].…”
Section: Protective and Prevention Effect Of Zinc Homeostasis On Lung...mentioning
confidence: 99%
“…Studies have shown that T cell development, differentiation, and activation are zinc-dependent processes [ 46 ]. In clinical trials, mild zinc deficiency in humans (3–5 mg/day) caused dysfunctions in Th1 and Th2, leading to a decline in cell-mediated immunity [ 47 ] However, in vitro and in vivo experiments demonstrated that therapeutic zinc supplements can mediate Th1 and Th2 immune functions and reduce Th2-mediated chronic airway inflammation by activating regulatory T cells [ 40 , 48 ]. Zinc in the lung tissue is regulated by zinc transporters and mainly binds to MT.…”
Section: Protective and Prevention Effect Of Zinc Homeostasis On Lung...mentioning
confidence: 99%
See 2 more Smart Citations
“…We have shown that for both native OVA and OVA 323–339 peptide, the OT-II TCR-transgenic epitope stimulated OT-II T cells more effectively in the presence of PM. OT-II transgenic mice have been commonly used as a model for studies on antigen-specific T cell responses in various contexts (Clemen et al 2021 ; Krone et al 2022 ). Our results exclude the effect of PM on antigen (Ag) processing, since OVA 323–339 peptide (epitope) presentation does not require any intracellular processing.…”
Section: Discussionmentioning
confidence: 99%